The Effect of Self-Efficacy, Soft Skills, And Fieldwork Practices On The Work Readiness Of Grade 12 Students of SMKN Negeri 2 Sewon, Bantul, Yogyakarta - Panandang, Puguh Johar; Epsilandri Septyarini; Nala Tri Kusuma (Journal of Economy, Accounting and Management Science (JEAMS), 2025)
This study aims to see whether Self-Efficacy, Soft Skills, and Field Work Practices affect Job Readiness. A descriptive quantitative approach was used in this study and questionnaires as a method of data collection. Grade 12 students of SMK Negeri 2 Sewon, Bantul as many as 237 students are the population in this study. The sampling technique in this study uses a simple random sampling technique. The sample in this study is 74 determined using the Slovin formula. The data in this study was processed using a data analysis tool, namely SPSS 27. The data processing method uses several linear regression analysis methods. The results of this study show that Self-Efficacy, Soft Skills, and Field Work Practices have a positive and significant influence on Job Readiness. In addition, Self-Efficacy, Soft Skills, and Field Work Practices simultaneously have a positive and significant effect on Job Readiness.  The implication of this research is that this research is expected to be a reference and evaluation material for SMK Negeri 2 Sewon in improving the ability and quality of students and in making decisions related to the program to be implemented so that the work readiness of SMK Negeri 2 Sewon students continues to increase.